The obesity–asthma link in different ages and the role of Body Mass Index in its investigation: findings from the Genesis and Healthy Growth Studies. Issue 10 (21st September 2013) - Guibas, G. V.; Manios, Y.; Xepapadaki, P.; Moschonis, G.; Douladiris, N.; Mavrogianni, C.; Papadopoulos, N. G.
Abstract Background To date, an obesity/asthma link is well defined in adults; however, the nature of such a link is obscure in children, partly due to Body Mass Index (BMI) limitations as a surrogate fat mass marker in childhood. We thus opted to investigate the association of adiposity with asthma in children of different ages, using several indices to assess fat mass. Methods Wheeze ever/in the last 12 months (current) and physician‐diagnosed asthma were retrospectively reported via questionnaire by the parents of 3641 children, participating in two cross‐sectional studies: 1626 children aged 2–5 (the Genesis Study) and 2015 children aged 9–13 (the Healthy Growth Study). Perinatal data were recorded from the children's medical records or reported by parents. Anthropometric measurements (i.e., BMI, waist/hip circumference, biceps/triceps/subscapular/suprailiac skinfold thickness) were conducted in both cohorts; bioelectric impedance analysis (BIA) was conducted only in preadolescent children. Results In children aged 2–5, asthma was positively correlated with conicity index, waist/hip circumference, waist‐to‐height ratio, skinfold thickness, and skinfold‐derived percentage fat mass (P < 0.05) but not BMI or BMI‐defined overweight/obesity, after adjusting for several confounders. In children aged 9–13, asthma was positively associated with conicity index, waist circumference, waist‐to‐height ratio, skinfold thickness, skinfold‐derived percentage fat mass, BIA‐derived percentage fat mass, BMI, and BMI‐defined overweight/obesity, following adjustment (P < 0.05). Current/ever wheeze was not consistently associated with fat mass in either population. Conclusions Fat mass is positively linked to asthma in both 2–5 and 9–13 age spans. However, the failure of BMI to correlate with preschool asthma suggests its potential inefficiency in asthma studies at this age range.